Suggestions for thought - Nightingale, Florence, 1820-1910 (Studies in health, illness, and caregiving., 1994)
Florence Nightingale is best known as the founder of modern nursing, a reformer in the field of public health, and a pioneer in the use of statistics. It is not generally known, however, that Nightingale was at the forefront of the religious, philosophical, and scientific though of her time. In a three-volume work that was never published, Nightingale presented her radical spiritual views, motivated by the desire to give those who had turned away from conventional religion an alternative to atheism. In this volume Michael D. Calabria and Janet A. Macrae provide the essence of Nightingale's spiritual philosophy by selecting and reorganizing her best-written treatments. The editors have also provided an introduction and commentary to set the work into a biographical, historical, and philosophical context. This volume illuminates a little-known dimension of Nightingale's personality, bringing forth the ideas that served as the guiding principles of her work. It is also an historical document, presenting the religious issues that were fiercely debated in the second half of the nineteenth century. In Suggestions for Thought, one has the opportunity to experience a great practical mind as it grapples with the most profound questions of human existence.